First Aid for Pesticide Exposure - Frederick M. Fishel (EDIS)
Pesticide poisoning is a commonly under-diagnosed illness. This 5-page fact sheet describes how to recognize the early symptoms of pesticide exposure and provide basic first aid for the treatment of victims. It explains how to provide initial treatment in the case of pesticide exposure on the skin, in the eye, through inhalation, and in the mouth or swallowed. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.